Experimental and Statistical Analysis of Bitumen's Field Ageing in Asphalt Pavements. Issue 7 (July 2022) - Zhang, Hanyu; Soenen, Hilde; Carbonneau, Xavier; Lu, Xiaohu; Robertus, Carl; Zhang, Yuqing
Field ageing gradients of bitumen samples recovered from 14 asphalt road sections were investigated via rheological and chemical characterizations and statistical analysis. The effects of air voids and environmental factors on the ageing gradient were evaluated using the field ageing and climate data. The effectiveness of the pressure ageing vessel (PAV) test was assessed in accelerating the bitumen's long-term ageing by comparing with the field ageing data. Critical factors for field ageing were identified using statistical methods. A statistical model for the Glover-Rowe (G-R) parameter was formulated and verified by incorporating the screened key factors. Results indicate that a threshold air void content (around 6%) exists in differentiating the field ageing gradient patterns in the asphalt pavements. An increasing tendency is observed between the ageing gradient and annual days below 0°C. The chemical indices, stiffness-related indices, and G-R parameter can quantify the field ageing gradient of asphalt pavements. The PAV test can condition the bottom slices' bitumen to the same ageing level as that in a pavement depth of 0.5–2 cm after 8 years' field service. Pavement service life, binder content, minimum temperature, days above 32°C, and days below 0°C are the critical material and environmental factors that significantly affect bitumen's complex shear modulus, crossover frequency, G-R parameter, and Δ Tc . The statistical model is verified with an acceptable mean absolute error of 28.1% and a R 2 value of 0.95.